ANALYSIS OF MARKETING STRATEGY FOR BOOK PRODUCTS THROUGH WEBSITE DESIGN WITH THE IMPLEMENTATION OF SALAM CONTRACTS AT IBN AZKA PRESS PUBLISHERS - Zakie Shiddieqi; Mukhamad Najib; Achmad Firdaus (Department Islamic Economics, 2026)
studies that specifically designed websites in the aspect of marketing strategy are still very limited. Therefore, the marketing strategy is used as an instrument in website design at the publisher Ibn Azka Press and also tries to apply the salam contract transaction model in its design. This study aims to formulate and create strategies through the website and propose a book selling model using a salam contract. The method used in this research is qualitative by using a descriptive approach and case studies. Data analysis using Pearson Product Moment and Cronbach Alpha. The results showed that the participants felt helped by the website sales system applied to the publisher of Ibn Azka Press because product information was easy to find. The application of the salam contract in this study emphasizes and explains to the general public, especially customers, in order to spread shariah knowledge about the salam contract.